Analisis Kemampuan Pemecahan Masalah MatematikaSiswa Berdasarkan Taksonomi Solo - SAFITRI, Elita; , Masduki, S.Si, M.Si (2016)
The purpose of this research is to describe the use of SOLO taxonomy to assess students' mathematical problem solving ability. This type of the research is a qualitative research. The observation time of this research is in the second semester of the 2015/2016 academic year. The subjects of the study were students of SMP Negeri 2 Colomadu. Technique of collecting data are using interviews, and documentation. The data collected are analyzed by using three grooves methods. The validity of the data in this research is using triangulation techniques and resources. The result of the study states (1) Students who are highly skilled based SOLO taxonomy can reach extended abstrack levels, capable of being at the level of relational, and poor performance at the level of multistruktural (2) the factors that causing the error: less accuracy, the calculation operation and the lack of understanding the material.